Composition, provenance, and tectonic setting of Ordovician siliciclastic rocks in the San Rafael block: Southern extension of the Precordillera crustal fragment, Argentina - Cingolani, Carlos Alberto (2003)
Sandstone petrography, geochemistry (major, trace, and rare earth elements [REE]), and Nd isotopic composition are presented for the siliciclastic Lower Caradoc Pavo´n Formation of the San Rafael block, central west Argentina. These constrain the provenance and tectonic setting of deposition and enable comparison to equivalent Ordovician units along the proto-Andean Gondwana margin. Most of the Pavo´n Formation sandstones are quartz-feldspathic wackes, composed of quartz, feldspars, and fragments of metaquartzitic rocks. The samples plot in the recycled orogen and continental block provenance fields of QFL diagrams. In view of the intense recycling and diagenetic processes, as indicated by CIA and CIW indices, diagrams involving immobile trace elements are considered better source indicators and suggest an active margin and island continental arc provenance. REE element distributions and initial 1Nd isotopic values (23.1 to 24.0) provide evidence of upper crust source materials. Nd TDM model ages for the provenance protolith are 1.4–1.5 Ga, consistent with a possible sediment source in Grenville-age rocks exposed in the Ponon Trehue area. The Pavo´n Formation was part of the sedimentary infill of a foreland basin generated and uplifted following accretion of the Precordillera terrane with the Gondwana active margin.